DIALEKTIKA PEMIKIRAN AL-GHAZALI DAN KURIKULUM PAI KONTEMPORER DALAM PENDIDIKAN AKHLAK - Alfin Siregar; Ahmad Ryan Htb (Yayasan Baitul Hikmah al-Zain, 2025)
This study explores Al-Ghazali’s perspective on moral education and its relevance to the contemporary Islamic Religious Education (PAI) curriculum. The main problem addressed is the lack of integration between classical moral values and the modern education system. The purpose of this research is to examine Al-Ghazali's concept of moral education and analyze its alignment with current PAI curriculum approaches. The method employed is qualitative descriptive through literature study. Data were collected from Al-Ghazali's works, classical Islamic literature, and recent PAI curriculum documents. The research finds that Al-Ghazali's emphasis on soul development, self-restraint, and habitual good deeds remains highly relevant in shaping students’ character today. The contemporary PAI curriculum can enhance its effectiveness by incorporating Al-Ghazali’s ethical-sufistic principles. These findings affirm the significance of preserving Islamic scholarly heritage to address current moral challenges in education.